The Design and Analysis of a Novel Vertical Axis Small Water Turbine Generator for Installation in Drainage Lines - Werayoot Lahamornchaiyakul; Nat Kasayapanand (International Journal of Renewable Energy Development, 2023)
The objective of this study was to determine the mechanical power efficiency of a novel vertical-axis small water turbine generator for installation in drainage lines. A 3D model was created to evaluate the performance of each design. The system was designed, analysed, and calculated for the most suitable geometries of the water inlet, drainage lines, main structure, and water turbine wheels using computational fluid dynamics software. The diameter of the water turbine wheel in the numerical model was 48 mm. The control volume technique was used in the numerical simulation method, and the k-epsilon turbulence model was employed to find the computational results. For the Computational Fluid Dynamics (CFD), the appropriate mash element for each model section was generated for numerical simulation, which showed that the torque from the water turbine modelling varied depending on the time domains and was related to speed relative to the developed force. The maximum torque and maximum power that a vertical-axis small water turbine for installation in a drainage line could generate at a maximum flow rate of 0.0030 m3/s were 0.55 N.m and 26.84 watts, respectively. Similarly, calculations with mathematical equations, found that the maximum mechanical power value after calculating the rate of loss within the pipe system was 12.95 watts. The forces generated by the speed and pressure of the fluid can then be applied to the structure of the water turbine wheel. The vertical-axis small water turbine for installation in a drainage line was analysed under its self-weight by applying a gravitational acceleration of 9.81 m/s2 in Solidworks Simulation software version 2022. The numerical simulations that resulted from this research could be used to further develop prototypes for small water turbines generating commercial electricity.